Technology-Supported Learning Approaches in Stoma Care Education for Nursing Students: A Systematic Review - Zeynep Mete Merdin; Hülya Bulut (Journal of Gazi University Health Sciences Institute, 2026)
This systematic review aimed to identify the technology-supported learning approaches used in stoma care education for nursing students, evaluate their effects on learning outcomes, and examine their implementation characteristics, advantages, and limitations. Methods: The review was conducted in accordance with the PRISMA guidelines and registered in PROSPERO (CRD420261395533). A systematic search of PubMed, Scopus, Web of Science, ScienceDirect, Google Scholar, and DergiPark databases was conducted to identify studies published between 2016 and 2026. Methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools, while risk of bias was evaluated using Cochrane RoB 2 and ROBINS-I tools. Results: A total of 11 studies met the inclusion criteria. Identified interventions included simulation-based education, virtual reality (VR), serious game-based web applications, web-supported education, online/video-based learning, and digital presentation methods. Most studies reported positive effects on learning outcomes, particularly knowledge acquisition and skill development. Simulation-based interventions were found to improve self-efficacy, self-confidence, and communication skills. High-fidelity simulation and standardized patient applications appeared to be more effective than low-fidelity approaches. Serious game-based and web-supported approaches were associated with improved knowledge retention and greater student engagement. Follow-up assessments in a limited number of studies suggested that technology-supported interventions may contribute to long-term knowledge retention. Conclusion: Technology-supported learning approaches appear effective in improving nursing students’ stoma care knowledge and skills. However, larger multicenter studies with longer follow-up periods are needed to strengthen the evidence.